Dual endovascular repair (coils and stent) of a true aneurysm of the gastroduodenal artery - Taboada, Carola Rubio (J Vasc Bras, 2020)
We report a case of an asymptomatic gastroduodenal artery aneurysm diagnosed in a 39 year-old woman. An abdominal ultrasound study showed an aneurysmal dilatation of the gastroduodenal artery with 2 x 2 cm diameter. To confirm this finding, she then underwent a computed tomography scan of the abdomen and pelvis that showed a saccular aneurysm of the gastroduodenal artery. A dual endovascular approach was used to exclude the aneurysm by stent-assisted coil embolization. Complete exclusion of the aneurysm sac was confirmed on final angiography. She was discharged from the hospital on postoperative day 1.